KARAKTERISTIK PEMIKIRAN USUL AL-FIQH IMAM AL-GHAZALI DALAM KITAB AL-MUSTASFA MIN ‘ILM AL-USUL - Ihasan Ihasan (Jurnal Keislaman, 2018)
Imam al-Ghazali is a writer and thinker encyclopedic. The work of al-Ghazali covers a wide range of scientific branches of Islam. Theology, philosophy,tasawwuf and jurisprudence (fiqh). Al-Ghazali describes the scientific conception ofusulal-fiqh, including definition of usul al-fiqh. Its position in the structure andscope os Islamic scholarship. Al-Ghazali defines the usul al-fiqh as a science thatexamines the sources (orgins) law, the terms of validity and model, structure andmethod of oppointment to the law. Usul al-fiqh as defined is a noble thought is ascience because it has the potential of combining reason and revelation. Disciplineis explicitly different from the science of kalam (theology) which is “kulli” anIslamic science that is particular, because it is concerted is a discussion on the legalarguments of personality. It’s as tafsir, hadith, and tasawwuf. In hierarchic usulalfiqhunder the umbrella of theology.